Breed-specific biochemical parameters of healthy adult turkeys in humid tropics in Nigeria - DANIEL-IGWE, G.; OKWARA, N. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study evaluated the serum biochemistry profile of apparently healthy B-not strain of indigenous turkeys and determined the influence of sex on parameters. A total of 50 apparently healthy B-not strain of turkeys of either sex were studied. The turkeys were kept in the animal house at the College of Veterinary Medicine in Michael Okpara University of Agriculture, Umudike, Abia State, Nigeria. Blood samples were collected from the jugular vein and standard procedures were followed in all the serum biochemistry parameters determined. The overall mean for the serum biochemistry parameters were as follows: alkaline phosphatase (ALP): 207.71 ± 2.93 IU/L, aspartate amino transferase (AST): 82.51 ± 1.13 IU/L, alanine amino transferase (ALT): 8.80 ± 0.83 IU/L, total protein: 3.69 ± 0.18 g/dl, albumin: 1.94 ± 0.54 g/dl, globulin: 1.75 ± 0.14 g/dl, cholesterol: 140.82 ± 5.28, bilirubin: 0.37 ± 0.07 mg/dl, urea: 4.29 ± 0.30 mg/dl, creatinine: 0.31 ± 0.38 mg/dl, triglycerides: 107.95 ± 7.55 mg/dl and glucose: 140.33 ± 0.52 mg/dl. In comparison to the female turkeys, the males had significant lower (p < 0.05) urea, cholesterol and triglycerides levels. It is thought that the baseline biochemical values will help veterinarians to interpret serum profile of sick animals and assist researchers in interpreting laboratory data.